COMPARATIVE ANALYSIS OF ONLINE STRATEGIES IMPLEMENTED BY FOUR UNIVERSITIES FROM ROMANIA - George, Schin (European Scientific Journal, ESJ, 2015)
The online promotion strategies play a crucial role in the positioning of higher education institutions on the global market. In this context, this paper aims at revealing he pillars of online strategies developed by four universities from Romania in order to outline their competitive identity both on the national and international educational services market. The research methodology involved in-depth analyses of these universities’ online strategies, by embedding their websites accessibility, design and interactivity, organization of content, SEO results, as well as their presence in social networks. The results emphasize relevant gaps in what concerns each university online promotion strategy, but also they lead to the formulation of best practices for the improvement of these strategies. The managerial implications are focused on proposals for decision makers reading the ways to promote the academic brands through multiple communication channels.